Effects of Saccharomyces cerevisiae-lactic acid bacteria cocultured maize silage on dairy cows performance and in vitro rumen fermentation - Chen, Qingqing; Liu, Zixin; Zhou, Chuanshe; Zhong, Zhiming; Wu, Jian; Jiang, Aoyu; Yang, Hai; Tan, Zhiliang; Lukuyu, Bernard Adubwa; Kang, Jinhe (Frontiers in Microbiology, 2026)
IntroductionMicrobial additives can improve silage quality in lowland areas. However, Saccharomyces cerevisiae and Lactic Acid Bacteriacan efficacy on whole-plant maize silage under Tibet’s hypoxic and cold environment, have not been explored.MethodsIn this experiment, whole corn plants cultivated in Dazi District, Lhasa City, Xizang (Tibet) Autonomous Region, were selected as silage raw materials. The treatment group was added 0.5 kg of microbial additives per ton of silage. The addition levels for both Saccharomyces cerevisiae and Lactic Acid Bacteria were ≥ 1 × 107 CFU·g-1 FM). The quality of silage and its in vitro fermentation characteristics were determined on 0, 30 and 60 days of fermentation, respectively. Subsequently, dairy cows were fed with silage after 60 days of fermentation to evaluate milk production and milk quality.ResultsThe results indicated that the lactic acid content in the treatment group was increased significantly on 30 and 60 days of fermentation (p < 0.05). In addition to Simpson’s index, alpha diversity was significantly affected by the fermentation day × treatment interaction (p < 0.05). At 60 days of fermentation, the abundance of Firmicutes phylum in the treatment group was significantly higher than that in the control group (p < 0.05). The abundance of genera such as Acetobacter and Latilactobacillus was significantly decreased (p < 0.05), while the abundance of the genus Weissella was significantly increased (p < 0.05). Dairy cows were fed 60-day maize silage, the milk protein content and total solid content in the treatment group were significantly higher than that in the control group (p < 0.05). The levels of dry matter degradation rate, ammonia nitrogen and total volatile fatty acids in the in vitro fermentation of maize silage in the treatment group on the 60th day of fermentation were significantly higher than that in the control group (p < 0.05).ConclusionIn Xizang (Lhasa, China), the addition of microbial additives has significantly improved the quality and nutritional value of whole corn silage plants and enhanced the milk quality of local dairy cows. This provides a theoretical basis for the application of microbial additives from the Qinghai-Tibet Plateau to agricultural crops.